One-Sided Nonlocal Boundary-Value Problem for Singular Parabolic Equations - Pukalskyi, I. D. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
In spaces of classical functions with power weight, we prove the existence and uniqueness of a solution of a one-sided nonlocal boundary-value problem for parabolic equations with an arbitrary power order of degeneracy of coefficients. We obtain an estimate for the solution of this problem in the corresponding spaces.